Incidencia política en el rol de la Silla Vacía y su influencia en la administración y gestión pública - Pucha Coronel, Magy Nallely (2023)
The present curricular research work entitled "Political Impact in the Role of the Empty Seat and Its Influence on Administration and Public Management" arises from the necessity to conduct a critical analysis of the significant political influence in spaces of citizen participation, with the Empty Seat being one of the most recurrent due to the structure of its function, the voting power it holds, and its control over deliberation. Likewise, it aims to analyze the violation of the right to participation and its effect on good public administration, from which we are entitled by law. It is important to emphasize that the objective is to determine the reasons behind the decrease in participation within this role, factors that even though they are minimal, still reveal the desire of third parties to obtain benefits, affecting the proper application of the equation citizens at different levels of state organization, resulting in more just, democratic, and socially responsible societies. The conducted study demonstrates that users of the Empty Seat at some point in this process felt vulnerable mainly because it is not a role of general knowledge as it should be. Therefore, accessing this Empty Seat was a challenge in every sense of the word. Additionally, participating in these spaces and encountering direct attacks from those who claim to be administrators of society, who do not ensure their participation or decision-making, and who seek to benefit from third parties, disregarding the principles of citizen participation, prevents them from enjoying the opportunities provided by the law. For the technical execution of this research work, the application of data collection methods became evident, allowing its development. Surveys and interviews were conducted with legal professionals, Council members of a Municipal Autonomous Decentralized Government, and users of the Empty Seat during the period from 2019 to 2021. The collected data served as the basis for the formulation of propositional guidelines with the sole purpose of guaranteeing the right to citizen participation, access, and timely engagement through a well-defined process that encompasses all user needs. This process aims to effectuate, prevent, and reduce the incidence of politicians and their party or personal benefits in these spaces that are meant to be democratic. 4 In conclusion, this research sheds light on the critical analysis of the political impact of the Empty Seat role, focusing on its influence on administration and public management. The study reveals the vulnerability felt by users due to limited general knowledge of the role, coupled with challenges encountered in participating in spaces of citizen participation. The findings emphasize the necessity of developing propositional guidelines to ensure citizen engagement, access, and timely participation. The practical implementation of these guidelines is crucial for maintaining democratic integrity and minimizing the influence of political interests in spaces that are meant to uphold democratic principles.